DO FUNDAMENTAL FINANCIAL RATIOS AFFECT THE COMPANY'S STOCK PRICE? INDONESIA EVIDENCE - Zarefar, Arumega; Armadani, Armadani (UI Scholars Hub, 2024)
The objectives of this research aims to examine the effect of corporate fundamental financial ratios on stock prices and to examine whether firm age determine stock prices in the perspective of signaling theory. Here Generalized Least Squares (GLS) approach was used as the main analysis technique, and Ordinary Least Squares (OLS) was incorporated for the robustness test. The research was conducted on companies listed on the Indonesia Stock Exchange during the 2014-2020 period. This study finds that return on assets, solvency ratio, and Tobin's Q positively affect stock prices, that cash ratio has a negative effect on stock prices, and that, interestingly, older companies convey better signals than the younger ones. These findings can assist investors in making quality decisions and company managers in making consideration for developing company strategies. Further, this study comprehensively analyzes the effect of corporate financial ratios on stock prices using the perspective of signaling theory and Modigliani-Miller theory looks at the differences between older and younger companies.